River of time : my descent into depression and how I emerged with hope - Judd, Naomi; Wilkie, Marcia (Center Street, 2016)
"The Grammy-winning superstar and best-selling author of All That Is Bitter and Sweet shares the story of her struggles with depression, PTSD and addiction, a journey that included extended hospital stays and moving lessons about how to find hope and help,"--NoveList.